Bridging the Gap Between Chemiluminescence Immunoassay and Liquid Chromatography‐Tandem Mass Spectrometry for Infliximab Monitoring: Method Validation and Clinical Comparability Study - Ying Xia; Ming‐Mei Zhu; Meng‐Qing Xiao; Chen‐Chun Zhong; Yu‐Jun Zhou; Yi‐Hao Xue; Shi‐Wei Zheng; Li Li; Feng Chen (Journal of Separation Science, 2026)
ABSTRACT Infliximab (IFX) is a cornerstone biologic for pediatric inflammatory bowel disease, where therapeutic drug monitoring (TDM) is essential but complicated by inter‐platform variability. Systematic comparison of automated immunoassays with reference methods is therefore warranted. This study aimed to validate an in‐house chemiluminescence immunoassay (CLIA) for IFX quantification and evaluate its agreement with liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). A CLIA kit was validated by assessing the limit of blank, specificity, linearity, accuracy, precision, matrix equivalence, and stability. IFX concentrations in 52 pediatric plasma samples were measured by CLIA and a reference LC‐MS/MS method. Comparability was evaluated using linear regression, Passing‐Bablok regression, and Bland‐Altman analysis. CLIA showed excellent performance (lower limit of quantification: 0.640 µg/mL; specificity 0.05). However, Bland‐Altman revealed substantial mean relative bias (67.9%) and poor categorical agreement (52% concordance) within the therapeutic range (3–7 µg/mL), indicating non‐interchangeability. We validated a rapid, automated CLIA suitable for high‐throughput TDM. Despite strong correlation, significant quantitative differences preclude direct result substitution, underscoring the need for method‐specific therapeutic thresholds.